2020
DOI: 10.1038/s41467-020-14697-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic POGZ mutation causes impaired cortical development and reversible autism-like phenotypes

Abstract: Pogo transposable element derived with ZNF domain (POGZ) has been identified as one of the most recurrently de novo mutated genes in patients with neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD), intellectual disability and White-Sutton syndrome; however, the neurobiological basis behind these disorders remains unknown. Here, we show that POGZ regulates neuronal development and that ASD-related de novo mutations impair neuronal development in the developing mouse brain and induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 71 publications
8
67
1
Order By: Relevance
“…We found that these mice exhibit altered behavior in a well-studied assay of anxiety-related avoidance, the elevated plus maze (EPM). Interestingly, this is similar to a recently published study which found evidence for decreased anxiety in Pogz mutants using the open field test ( Matsumura et al, 2020 ). We then studied communication between the ventral hippocampus (vHPC) and medial prefrontal cortex (mPFC), which is known to be necessary for normal anxiety-related avoidance in the EPM.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that these mice exhibit altered behavior in a well-studied assay of anxiety-related avoidance, the elevated plus maze (EPM). Interestingly, this is similar to a recently published study which found evidence for decreased anxiety in Pogz mutants using the open field test ( Matsumura et al, 2020 ). We then studied communication between the ventral hippocampus (vHPC) and medial prefrontal cortex (mPFC), which is known to be necessary for normal anxiety-related avoidance in the EPM.…”
Section: Introductionsupporting
confidence: 92%
“…Interestingly, another study characterizing mice with heterozygous disruptions of Pogz was recently published ( Matsumura et al, 2020 ). These Pogz mutant mice spent more time in the center of an open field, less time sniffing novel mice, and more time grooming, compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…AAV9-PHP.eB virus expressing mCherry and the gRNA targeting Pogz was delivered to a transgenic mouse line that constitutively expresses CAS9 protein ( Chiou et al, 2015 ). Because Pogz functions as a negative regulator of transcription and plays crucial roles in embryogenesis, transgenic mice (homozygous for either gene deletion or LoF point mutation) were 100% prenatally lethal ( Matsumura et al, 2020 ; Gudmundsdottir et al, 2018 ). In contrast, Pogz iCAP mice that were identified by mCherry+ under the fluorescent lamp at P1 were viable and showed no signs of evident developmental impairments.…”
Section: Resultsmentioning
confidence: 99%
“…Another top ASD gene, POGZ (Pogo transposable element-derived protein with zinc finger domain; OMIM 616364; [ 26 , 27 , 28 , 37 ]), also favors neuronal differentiation by inhibiting the Notch signaling. IUE-mediated knockdown of Pogz leads to an increased proportion of NSCs, and reduced IPs and late-born neurons [ 130 ]. A murine Pogz rescued this phenotype, while mutants carrying ASD pathogenic mutations did not [ 130 ].…”
Section: Asd Risk Converging On Cortical Development—evidence Frommentioning
confidence: 99%
“…IUE-mediated knockdown of Pogz leads to an increased proportion of NSCs, and reduced IPs and late-born neurons [ 130 ]. A murine Pogz rescued this phenotype, while mutants carrying ASD pathogenic mutations did not [ 130 ]. In line with these data, NSCs derived from induced pluripotent stem cells of a patient with ASD carrying a de novo missense mutation in POGZ also show increased proliferation and reduced degree of neuronal differentiation [ 130 ].…”
Section: Asd Risk Converging On Cortical Development—evidence Frommentioning
confidence: 99%